Adaptasi dan Kesejahteraan Pekerja di Era COVID-19: - REGY CITRA PERDANA; DEDI HARTAWAN; RATNA SARI; MUHAMMAD RISQI AGUSTINO; YOSART ADI SUYOSO (Entrepreneurship Faculty, Universitas Garut, 2020)
Abstract Alert and always adaptive is the key for an organization or company to survive in the current pandemi COVID-19. This pandemic becomes an unexpected external crisis and is beyond anyone's prediction, making high uncertainty not only for the sustainability of the organization also becomes uncertainty for the workforce/individuals within it. Organizations are required to have directions and ways to deal with pandemics that have never happened before, so that many new solutions are found in dealing with impacts that arise when the organization's operations run in the middle of a pandemic. This article focuses on discussing some of the challenges and implications of the impact caused by COVID-19 in human resource (HR) science. The workforce must be assisted by the organization in adjusting and adapting to the new work environment. This research also directs some suggestions for future research so as to create sustainability and integrated research to overcome the challenges that are further investigated. Keywords: Adaptation, Pandemic COVID-19, workers, organizations